Teachers’ Teaching Creativity at Language Development Center of IAIN Padangsidimpuan - Sokhira LindaVinde Rambe; Sri Minda; Khoiriyah Shofiah; Khairani Khairani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
Teachers’ teaching creativity could facilitate effective learning and influence students’ learning motivation. It also creates the classroom not only just teaching, giving knowledge, and transferring information, but it also can give interest and extra experiences for students. The aim of this study was to investigate how teachers implemented their teaching creativity in EFL context. Then, this study was in a form of qualitative research applying descriptive method in analyzing the data. Five qualified English teachers at Language Development Center of State Institute for Islamic Studies Padangsidimpuan were purposively chosen as participants of the research. In addition, observation and interview were conducted to collect the data related to the implementation of teachers’ creativity in teaching English, and descriptive data analysis was used in analyzing them. Finally, related to the finding, this study conveyed that teachers’ teaching creativity was resulted from teachers’ sharing session and teaching observation. Then, teaching creativity were seen from several aspects; teachers often applied various “ice breaker” activity, they always implemented games in teaching, the teachers also could develop meaningful and contextual material, and they could make use limited media becoming useful and interesting.